Piloting a Mobility Tech Role at an Academic Medical Center. Issue 6 (November 2022) - James, David; Harrell, Shari; Labbe, Valerie; Ray, Midge
ABSTRACT: Introduction: There is often a breakdown in communication between physical therapy and nursing regarding the responsibility of patient mobility. This communication problem contributes to mobility being the most frequently missed clinical intervention. To address this gap, a Mobility Tech (MT) role was implemented at a large academic medical center. The purpose of this article is to describe the implementation of this role. Methods: Using the Institute for health care improvement (IHI) model for improvement, iterative small tests of change were developed to integrate the MT role on four acute care units. Using process flow mapping, the team developed a MT workflow that was adapted to create MT protocols. Results: Program outcomes included fall rates and the highest level of mobility documented by staff. During the MT pilot from February 2020 through June 2020, MTs provided an average of over 500 interventions each month. There was a clinically and statistically significant increase in mobility noted in two of the four pilot units. Conclusion: We have demonstrated that MTs can be safely incorporated into acute care nursing workflow, and comments from staff and patients validate the role is "value added."